(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Matviychyna S. V. Formation of interactive didactic socio-cultural environment as a condition of self-identity students of colleges The article investigates the nature of scientific categories of «socio-cultural environment» and «interactive socio-cultural environment». The main approaches to the content of these scientific definitions. The analysis of the essence in terms of psychology and pedagogy. The main focus is on the analysis of scientific approaches to the content that they put in the interactive interpretation of socio-cultural environment as an important didactic terms, which has a significant impact on stimulating self-identity of students enrolled in colleges.